Accumulation of alpha-synuclein pathology in the liver exhibits post-translational modifications associated with Parkinson’s disease - Martin Hallbeck; Sara Ekmark-Lewén; Philipp J. Kahle; Martin Ingelsson; Juan F. Reyes (iScience)
Summary: Accumulating evidence demonstrates that alpha-synuclein (α-syn) pathology associated with Parkinson’s disease (PD) is not limited to the brain, as it also appears in a select number of peripheral tissues including the liver. In this study, we identified a number of PD-associated α-syn post-translational modifications in the livers of (Thy-1)-h[A30P] mice, a mouse model of familial PD expressing human α-syn harboring the A30P mutation driven by a neuron-specific promoter. Ex vivo, we also demonstrate that human hepatocytes induce post-translational modifications following α-syn fibrillar (PFF) treatment. Moreover, such cells also degrade PFFs over time, whereas oligomeric assemblies are more resistant to degradation, but this process can be enhanced by autophagy stimulators. Collectively, our findings suggest that pathological α-syn is transported to the liver in a modified state or is modified upon arrival, which facilitates its clearance and detoxification, pointing to a role for the liver in the degradation of PD-associated pathology.